2018
DOI: 10.1111/ijtd.12140
|View full text |Cite
|
Sign up to set email alerts
|

The revised learning transfer system inventory in Portugal

Abstract: Although training is critical to leverage performance and competitiveness, it has been reported that only a part of learned skills is transferred to the workplace, reinforcing the need for a deeper understanding of the transfer process. The purpose of this study is to validate the revised learning transfer system inventory (LTSI) in Portugal. LTSI was administrated to 403 participants from five organizations operating in Portugal, upon completion of training programs. Exploratory and confirmatory analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(68 reference statements)
1
5
0
3
Order By: Relevance
“…These two results, interpreted together, could suggest the multidimensionality of support (Ford et al, 2018) or the overlap between the two constructs. Similar results have been found in Portugal, where supervisory support did not emerge with the application of the LTSI (Antunes et al, 2018). Cultural variation was proposed as a possible explanation, as power distance and paternalism were considered high in Portugal (Hofstede et al, 2010), which could have had an impact on the construct.…”
Section: Predicting Transfer Instrumentssupporting
confidence: 72%
See 1 more Smart Citation
“…These two results, interpreted together, could suggest the multidimensionality of support (Ford et al, 2018) or the overlap between the two constructs. Similar results have been found in Portugal, where supervisory support did not emerge with the application of the LTSI (Antunes et al, 2018). Cultural variation was proposed as a possible explanation, as power distance and paternalism were considered high in Portugal (Hofstede et al, 2010), which could have had an impact on the construct.…”
Section: Predicting Transfer Instrumentssupporting
confidence: 72%
“…However, there are still some issues to study, such as the conceptualization of the traditional factors as multidimensional constructs (Ford et al, 2018), the move towards a more consumer-centric inquiry (Baldwin et al, 2017), or the comparative study of training transfer. While international results have pointed to the potential existence of underlying factors of transfer that migrate across cultures (Antunes et al, 2018;Bates et al, 2012;Soerensen et al, 2017;Velada et al, 2009;Yamnill and McLean, 2005), other studies have suggested that factors could be more contingent to the context (Antunes et al, 2018;Soerensen et al, 2017). Most of the reported studies were conducted in English-speaking countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sendo assim, permitiu identificar as potenciais e reais dificuldades na transferência de treinamento no setor público, contribuindo com pesquisas recomendadas por Ford, Baldwin & Prasad (2018) e Antunes, Nascimento, & Bates (2018).…”
Section: Conclusõesunclassified
“…No entanto, apesar dos elevados investimentos em treinamentos, ainda há o desafio relacionado à sua transferência para o trabalho (Baldwin, Ford, & Blume, 2017), de modo que as organizações possam ser beneficiadas, devido ao fato de que as competências treinadas não são aplicadas (Hughes et al 2018). Antunes, Nascimento, & Bates (2018) reforçam a necessidade de conhecimento mais aprofundado acerca da transferência de treinamento, em função de que apenas parte das competências ensinadas serem transferidas ao trabalho. Neste sentido, conhecer as informações que influenciam na transferência de treinamento permitirá o aumento do rendimento dos investimentos em treinamentos realizados pelas organizações, uma vez que será possível planejar e executar as iniciativas adequadamente (Ford, Baldwin, & Prasad, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation